A Scientific Rationale for Using Cystic Fibrosis Transmembrane Conductance Regulator Therapeutics in COVID-19 Patients - Lidington, Darcy; Bolz, Steffen-Sebastian (Frontiers in Physiology, 2020)
Several pathological manifestations in corona virus disease 2019 (COVID-19), including thick mucus, poor mucociliary clearance and bronchial wall thickening, overlap with cystic fibrosis disease patterns and may be indicative of “acquired” cystic fibrosis transmembrane conductance regulator (CFTR) dysfunction. Indeed, tumor necrosis factor, a key cytokine driving COVID-19 pathogenesis, down-regulates lung CFTR protein expression, providing a strong rationale that acquired CFTR dysfunction arises in response to lung inflammation. In this perspective, we propose that CFTR therapeutics, which are safe and generally well tolerated, may provide benefit to COVID-19 patients. Although CFTR therapeutics are currently only approved for treating cystic fibrosis, there are efforts to repurpose them for conditions with “acquired” CFTR dysfunction, for example, chronic obstructive pulmonary disease. In addition to targeting the primary lung pathology, CFTR therapeutics may possess value-added effects: their anti-inflammatory properties may dampen exaggerated immune cell responses and promote cerebrovascular dilation; the latter aspect may offer some protection against COVID 19 related stroke.